2009
DOI: 10.1002/jcb.22439
|View full text |Cite
|
Sign up to set email alerts
|

A single deletion at position 134, 135, or 136 in the beta 7–beta 8 loop of the p51 subunit of HIV‐1 RT disrupts the formation of heterodimeric enzyme

Abstract: The human immunodeficiency virus type 1 reverse transcriptase (HIV-1 RT) is a heterodimeric enzyme composed of p66 and p51 subunits. Earlier, we showed that the beta7-beta8 loop of p51 is crucial for polymerase activity of HIV-1 RT as either deletion or Ala substitution of amino acids in the beta7-beta8 loop spanning residues 136-139 in the p51 subunit impaired dimerization and, in turn, polymerase function of the enzyme (Pandey et al. 2001 Biochemistry 40: 9505-9512). In the present study, we generated subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The TSAO molecules in the model and in the crystal structure are positioned on either side of Glu138 which suggests that Glu138 plays an important role in the entry of TSAO compounds to the NNIBP. Mutation of the neighboring conserved residue Asn136 (p51) also causes resistance to TSAO 41 ; like Glu138, Asn136 is located at the p66/p51 dimer interface and deletion of Asn136 is deleterious for the stability of the RT heterodimer 42 . A Cα superposition of RT: 7 and RT: 5 9 structures showed that the 136-138 loop had deviated the most (~2 Å) compared to other amino acid residues of p51 at the dimer interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSAO molecules in the model and in the crystal structure are positioned on either side of Glu138 which suggests that Glu138 plays an important role in the entry of TSAO compounds to the NNIBP. Mutation of the neighboring conserved residue Asn136 (p51) also causes resistance to TSAO 41 ; like Glu138, Asn136 is located at the p66/p51 dimer interface and deletion of Asn136 is deleterious for the stability of the RT heterodimer 42 . A Cα superposition of RT: 7 and RT: 5 9 structures showed that the 136-138 loop had deviated the most (~2 Å) compared to other amino acid residues of p51 at the dimer interface.…”
Section: Resultsmentioning
confidence: 99%
“…Alteration of the loop has been shown to disrupt p66/p51 dimerization 42 . In the TSAO-T-bound structure, two β-sheets (β6-β10-β9 and β12-β13-β14) are wide apart causing a significant long-range distortion of the RT structure (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the ␤7-␤8 loop spanning amino acids 133 to 140 of the HIV-1 RT p51 subunit participates in forming the floor of the NNRTI binding platform in the RT crystal structure (17) and helps to maintain the stable, functional heterodimeric enzyme (39,40,49). Subunit-selective mutagenesis also showed that the E138K mutation confers resistance to TSAO compounds through the p51 subunit (8, 11); however, no experimental data have been available until now in regard to secondgeneration NNRTIs.…”
Section: Discussionmentioning
confidence: 99%
“…In the heterodimer structure, pdb: 1DLO (Hsiou et al, 1996), the Ile382 δ-methyl is positioned 5.6Å from the sidechain carbonyl oxygen of Asn136 on the p51 subunit. The Asn136 residue on p51 and the loop containing it have been shown to play an important role in dimerization (Balzarini et al, 2005;Mulky et al, 2007;Upadhyay et al, 2010). Based on the behavior of the Ile382E resonance, this interface is formed at a sufficiently early stage so that it is largely present during the first 2D 1 H-13 C HMQC accumulation period of 5.5 hr.…”
Section: Formation Of the P66:p66' Interfacementioning
confidence: 99%